Cobertura midiática do Sistema Único de Saúde no Brasil: um recorte histórico - Miranda, Lana Cristina Bueno (2019)
Contemporary society has witnessed the growth of the information flow at an enormous rate. The growing dissemination of information and data by the mass media covers diverse topics with little or no concern for the quality, truthfulness and context of the news presented. Studies have exposed the relationship between the media and health issues, evidencing the hypervaluation of irrelevant themes and the media silencing about important concerns. Considering the relationship between the media and the Unified Health System, this research aimed to investigate how the SUS image was built by the media at the time of its creation and as it is currently being conceived. For that, a survey and analysis of news and published reports about SUS was carried out in a newspaper and a magazine of great circulation in Brazil, in two periods, from January 1988 to December 1991 and from March 2016 to March 2018. The comparative study of these historical data made it possible to understand the socio-political context of the SUS and to identify the main issues addressed by the media throughout the during the study periods, leading to reflections and contributing to the consolidation and strengthening of SUS in its current scenario.